Penerapan Model Make a Match dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SDN Boloagung 02 - Lestari, Sinta Devi; khamdun, Khamdun; Riswari, Lovika Ardana (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Think deeply and be able to express opinions from his thoughts with a group learning model that requires students to be active and cooperate with their group mates to develop their abilities. Application of Make a Match learning model in improving students ' critical thinking skills and teaching skills of teachers on fractional material. This class action research was conducted in Class V of SD Negeri Boloagung 02 with a subject of 28 students and teachers which lasted for 2 cycles. Each cycle consists of two meetings. The dependent variable is the critical thinking ability of students, while the independent variable is the Make a Match learning model. Data collection techniques used are interviews, observations, tests, and documentation. The results obtained that students critical thinking skills after the implementation of Make a Match model, in the first cycle obtained a value of 72.0 with a percentage of 72% and students completed as much as 68%. Improvement of critical thinking skills in the second cycle obtained a value of 83.04 with a percentage of 83% and the percentage of students obtained mastery of 89%. The application of Make a Match model on fraction material can improve students 'critical thinking skills and teachers' teaching skills. Therefore, in learning, teachers are advised to use the Make a Match model to the maximum so that students are more excited, enthusiastic, and play an active role in the learning process.